Molecular response to multiple trace element contamination of the European sardine - Beauvieux, Anaïs; Fromentin, Jean-Marc; Saraux, Claire; Romero, Diego; Couffin, Nathan; Brown, Adrien; Metral, Luisa; Bertile, Fabrice; Schull, Quentin (Peer Community Journal)

(untitled)
In marine ecosystems, the presence of trace elements resulting from anthropogenic activities has raised concerns regarding their potential effects on marine organisms. This study delves into the intricate relationship between trace element contamination and the physiological responses of a key marine species in the Mediterranean Sea: the European sardine. Since 2008, this species has been experiencing a significant crisis in the region, prompting numerous studies to investigate the potential factors behind the dramatic decline in sardines size, age, and body condition. However, thorough information on chemical contamination by trace elements and its physiological impact on this species was lacking. We found evidence for the accumulation of multiple elements in sardines, with a light East-West contamination gradient within the Gulf of Lions. While macro-physiological parameters (i.e. body condition) were not affected by contamination, pathways involved in cellular organization and response to stress were clearly upregulated, particularly in the liver, but also in muscle. In addition, a global upregulation in processes linked to the immune system, lipid homeostasis and oxidative stress was recorded in the liver. The associated energetic cost may add a substantial burden to sardines that already face multi-factorial constraints. This study also allows to pinpoint biomarkers of exposure and effects that may be important for monitoring Mediterranean sardine health. The results of this study and particularly the complex changes in protein expression demonstrate the need for future studies to test the concomitant effects of multiple stressors acting simultaneously, including large scale contamination.